The Role of Dikopukmtk Bukittinggi in Empowering Small and Medium Enterprises (SMEs) in Bukittinggi City in the Post-COVID-19 Pandemic Era - Debbi Kurnia Sari; Fachri Adnan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This study examines the role of the Office of Cooperatives, Micro, Small, and Medium Enterprises (Diskopukmtk) in Bukittinggi City in developing UMKM post-COVID-19. The research aims to analyze the supporting and inhibiting factors in empowering UMKM through various roles played by Diskopukmtk, such as facilitating funding, coaching, mentoring, and product marketing. The method used in this research is descriptive qualitative with a case study approach involving interviews with UMKM actors and related parties in Bukittinggi City.The findings reveal that Diskopukmtk plays a crucial role in enhancing MSME capacity through programs like interest-free loans, training to improve skills and knowledge of UMKM actors, and mentoring focused on business development and job creation. However, significant challenges include limited funding, insufficient human resources, weak marketing networks, and the negative impact of free markets. Despite these challenges, with strong regulatory and policy support from local governments, UMKM are expected to continue growing and improving their competitiveness. This research contributes to understanding the dynamics of UMKM empowerment in the post-pandemic era and highlights the importance of local government roles in supporting the sustainability of the UMKM sector.